Sepsis and Critical Illness Research Center investigators: protocols and standard operating procedures for a prospective cohort study of sepsis in critically ill surgical patients - Loftus, Tyler J; Mira, Juan C; Ozrazgat-Baslanti, Tezcan; Ghita, Gabriella L; Wang, Zhongkai; Stortz, Julie A; Brumback, Babette A; Bihorac, Azra; Segal, Mark S; Anton, Stephen D; Leeuwenburgh, Christiaan; Mohr, Alicia M; et al. (BMJ open, 2017)
IntroductionSepsis is a common, costly and morbid cause of critical illness in trauma and surgical patients. Ongoing advances in sepsis resuscitation and critical care support strategies have led to improved in-hospital mortality. However, these patients now survive to enter state of chronic critical illness (CCI), persistent low-grade organ dysfunction and poor long-term outcomes driven by the persistent inflammation, immunosuppression and catabolism syndrome (PICS). The Sepsis and Critical Illness Research Center (SCIRC) was created to provide a platform by which the prevalence and pathogenesis of CCI and PICS may be understood at a mechanistic level across multiple medical disciplines, leading to the development of novel management strategies and targeted therapies.MethodsHere, we describe the design, study cohort and standard operating procedures used in the prospective study of human sepsis at a level 1 trauma centre and tertiary care hospital providing care for over 2600 critically ill patients annually. These procedures include implementation of an automated sepsis surveillance initiative, augmentation of clinical decisions with a computerised sepsis protocol, strategies for direct exportation of quality-filtered data from the electronic medical record to a research database and robust long-term follow-up.Ethics and disseminationThis study has been registered at ClinicalTrials.gov, approved by the University of Florida Institutional Review Board and is actively enrolling subjects. Dissemination of results is forthcoming.